2005
DOI: 10.1182/blood-2005-04-1530
|View full text |Cite
|
Sign up to set email alerts
|

Activated platelets induce Weibel-Palade–body secretion and leukocyte rolling in vivo: role of P-selectin

Abstract: The presence of activated platelets and platelet-leukocyte aggregates in the circulation accompanies major surgical procedures and occurs in several chronic diseases. Recent findings that activated platelets contribute to the inflammatory disease atherosclerosis made us address the question whether activated platelets stimulate normal healthy endothelium. Infusion of activated platelets into young mice led to the formation of transient platelet-leukocyte aggregates and resulted in a several-fold systemic incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
159
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(174 citation statements)
references
References 51 publications
8
159
1
2
Order By: Relevance
“…40 Immunohistochemical staining showed significant platelet deposition in the medial layer and on the luminal surface of the 1-day denudated carotid artery (see Supplemental Figure S1B, panel a, at http://ajp.amjpathol.org). P-selectin staining was restricted to the luminal surface (see Supplemental Figure S1B, panel b, at http://ajp.amjpathol.org), which is consistent with the known propensity of activated platelets to shed P-selectin 41 and supported by immunostaining data in a recent report. 42 These results suggest that activated platelets may provide an adhesive surface, mediating leukocyte rolling adhesion potentially through the interaction of P-selectin expressed on activated platelets with its ligand PSGL-1 expressed by leukocytes.…”
Section: Platelet Deposition and Activation Supports The Early Recruisupporting
confidence: 71%
“…40 Immunohistochemical staining showed significant platelet deposition in the medial layer and on the luminal surface of the 1-day denudated carotid artery (see Supplemental Figure S1B, panel a, at http://ajp.amjpathol.org). P-selectin staining was restricted to the luminal surface (see Supplemental Figure S1B, panel b, at http://ajp.amjpathol.org), which is consistent with the known propensity of activated platelets to shed P-selectin 41 and supported by immunostaining data in a recent report. 42 These results suggest that activated platelets may provide an adhesive surface, mediating leukocyte rolling adhesion potentially through the interaction of P-selectin expressed on activated platelets with its ligand PSGL-1 expressed by leukocytes.…”
Section: Platelet Deposition and Activation Supports The Early Recruisupporting
confidence: 71%
“…At high shear conditions, platelet adhesion to EC is a prerequisite for leukocyte adhesion, and inhibition of platelets adhesion with specific antibodies is accompanied by a significant reduction in the number of adherent leukocytes. These findings are well comparable to observations of leukocyte-endothelium-interactions in mice in vivo [28,29].…”
Section: Fig (2) Specificity Of Cell-surface Interactionsupporting
confidence: 80%
“…These cell adhesion molecules are known for mediating leukocyte rolling on endothelial cells and platelet-leukocyte aggregation. 7,23,26 Studies have shown that elevated levels of selectins are present in the serum of subjects experiencing an inflammatory state. 30 P-selectin, in particular, is an important disease marker as it plays an essential role in many inflammatory processes including cancer, coronary artery disease, stroke, and diabetes.…”
Section: Vascular Targetingmentioning
confidence: 99%